A standardized assessment of forest mammal communities reveals consistent functional composition and vulnerability across the tropics. Issue 1 (5th November 2019) - Rovero, Francesco; Ahumada, Jorge; Jansen, Patrick A.; Sheil, Douglas; Alvarez, Patricia; Boekee, Kelly; Espinosa, Santiago; Lima, Marcela Guimarães Moreira; Martin, Emanuel H.; O'Brien, Timothy G.; Salvador, Julia; Santos, Fernanda; et al.
Abstract : The understanding of global diversity patterns has benefitted from a focus on functional traits and how they relate to variation in environmental conditions among assemblages. Distant communities in similar environments often share characteristics, and for tropical forest mammals, this functional trait convergence has been demonstrated at coarse scales (110–200 km resolution), but less is known about how these patterns manifest at fine scales, where local processes (e.g. habitat features and anthropogenic activities) and biotic interactions occur. Here, we used standardized camera trapping data and a novel analytical method that accounts for imperfect detection to assess how the functional composition of terrestrial mammal communities for two traits – trophic guild and body mass – varies across 16 protected areas in tropical forests and three continents, in relation to the extent of protected habitat and anthropogenic pressures. We found that despite their taxonomic differences, communities generally have a consistent trophic guild composition, and respond similarly to these factors. Insectivores were found to be sensitive to the size of protected habitat and surrounding human population density. Body mass distribution varied little among communities both in terms of central tendency and spread, and interestingly, community average body mass declined with proximity to human settlements. Results indicate predicted trait convergence among assemblages at the coarse scale reflects consistent functional composition among communities at the local scale, suggesting that broadly similar habitats and selective pressures shaped communities with similar trophic strategies and responses to drivers of change. These similarities provide a foundation for assessing assemblages under anthropogenic threats and sharing conservation measures.